2019
DOI: 10.1088/1674-1137/43/3/034104
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting hidden-charm pentaquarks from QCD sum rules

Abstract: We revisit the hidden-charm pentaquark states Pc(4380) and Pc(4450) using the method of QCD sum rules by requiring the pole contribution to be larger than or around 30% to better insure the one-pole parametrization to be valid. We find two mixing currents and our results suggest that the Pc(4380) and Pc(4450) can be identified as hidden-charm pentaquark states having J P = 3/2 − and 5/2 + , respectively, while there still exist other possible spin-parity assignments, such as J P = 3/2 + and J P = 5/2 − , which… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 75 publications
3
9
0
Order By: Relevance
“…In Refs. [63][64][65] we have found that these three configurations can be related as a whole, while in the present study we shall further find that two of them are already enough to be related to each other, just with the color-octetcolor-octet meson-baryon terms included. Using these relations, we shall study strong decay properties of P c states as D ( * ) Σ c molecular states.…”
Section: Introductionsupporting
confidence: 54%
“…In Refs. [63][64][65] we have found that these three configurations can be related as a whole, while in the present study we shall further find that two of them are already enough to be related to each other, just with the color-octetcolor-octet meson-baryon terms included. Using these relations, we shall study strong decay properties of P c states as D ( * ) Σ c molecular states.…”
Section: Introductionsupporting
confidence: 54%
“…There is still a place for the P c (4380), that is to be interpreted as the [Σ c D * − ] bound state with J P = 3/2 − . There exist more possible interpretations with the positive-parity assignments [11,34]. To clearly understand their nature, one still needs further experi-mental information.…”
Section: Currentmentioning
confidence: 99%
“…The main decay channels of Λcc(4550) areD ( * ) Ξ or the mixture of them [37,38]. Secondly, they are considered in constituent quark model [39][40][41][42], diquarkdiquark-antiquark picture [43][44][45][46][47], and diquark-triquark picture [48]. Thirdly, the narrow peak of P c (4450) might result from triangle singularity (TS) effect [49][50][51], which is purely kinematic effect, although for some quantum numbers of the P c state preferred in Ref.…”
mentioning
confidence: 99%